Strength of nervous system excitement processes and personality trace of Physical Education students from Santa Maria Federal University (UFSM) - Maria Cristina Chimelo Paim; Iouri Kalinine (Journal of Physical Education (Maringá), 2008)
The aim of this study is to verify the relationship between the strength of nervous system excitement and the personality trace – extroversion / introversion. From a sample of 240 Physical Education university students, 121 were male and 119 female. The methods used were “Strelau’s questionnaire” aiming at diagnosing the indexes of the excitement process strength, and “Eysenck’s questionnaire” aiming at diagnosing the indexes of extroversion and introversion. Results show that the strength of excitement processes connected significantly with the extroversion/introversion personality trace in male subjects (r=0.36, p < 0.001) and in female subjects (r=0.46, p < 0.001). The study points out that Physical Education male and female students (from UFSM) also tend to indicate higher extroversion/introversion indexes and that the strength of excitement processes is a peculiarity of the nervous system influential in developing extroversion/introversion personality trace.